EVALUASI PELAKSANAAN PROGRAM JAMINAN KESEHATAN DAERAH DI KABUPATEN MAGELANG - , Bambang Prihutomo; , Prof. dr. Ali Ghufron Mukti, M.Sc, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Verse 28H of the 1945 Constitution mandates that every community is entitled for social security in order to develop oneself fully as a dignified human being. To meet the mandate of Law Number 40 in the year of 2004 the government established National Health Insurance program Jamkesmas. This is because of the poor more numerous than the quota provided so that not everyone can be served with Jamkesmas, therefore local government must provide health insurance for the poor who do not involved in Jamkesmas quota through Jamkesda program. In order to assess the successful of the programs which already implemented it is necessary to have evaluation on the implementation of the Local health insurance program. Objective: This study was aimed to examine how the implementation of Jamkesda is, from the aspects of: 1) policy, 2) membership management, 3) service management, 4) financial management. Method : This was a qualitative research with cross sectional design. The subject of this study is stake holder who correlates with health financing issues including: Parliament, Bapeda, Health Offices, Head of the Health Center and Village Heads. Qualitative data was obtained through in-depth interviews with informants. Result : Policy implementation of Jamkesda Magelang has been well responded and marked by the publication of Perbup number 23 year of 2010. The participants of Jamkesda is the poor who do not included in Jamkesmas quotas which established by the Regent Decree. However, because there was no membership card available, Jamkesda service was not optimal. Jamkesda services are widely used for inpatient services whereas there was no outpatient care since there was no card available and a bureaucratic service procedure. Conclusion: Magelang district had the role of achieving universal coverage with the implementation of Jamkesda. Jamkesda policy was supported by the Regent Decree and hence, operational guidelines and technical guidelines are necessary for its optimal implementation.